2014
DOI: 10.18632/oncotarget.2180
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting DNA repair in adult high grade gliomas for patient stratification in the post-genomic era

Abstract: Deregulation of multiple DNA repair pathways may contribute to aggressive biology and therapy resistance in gliomas. We evaluated transcript levels of 157 genes involved in DNA repair in an adult glioblastoma Test set (n=191) and validated in ‘The Cancer Genome Atlas’ (TCGA) cohort (n=508). A DNA repair prognostic index model was generated. Artificial neural network analysis (ANN) was conducted to investigate global gene interactions. Protein expression by immunohistochemistry was conducted in 61 tumours. A fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…However, even if the mutator role of MGMT hypermethylation appears modest, it may have a relevant prognostic value. Recent clinical studies showed that methylation of MGMT is a useful predictor of the responsiveness of tumors to alkylating agents in gliomas [ 45 , 46 ], and is associated with good survival in patients treated with multidrug regimens [ 47 ]. It also predicts the response to the alkylating drug dacarbazine in metastatic CRC [ 48 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even if the mutator role of MGMT hypermethylation appears modest, it may have a relevant prognostic value. Recent clinical studies showed that methylation of MGMT is a useful predictor of the responsiveness of tumors to alkylating agents in gliomas [ 45 , 46 ], and is associated with good survival in patients treated with multidrug regimens [ 47 ]. It also predicts the response to the alkylating drug dacarbazine in metastatic CRC [ 48 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies showed that methylation of MGMT is a useful predictor of the responsiveness of tumors to alkylating agents in gliomas [ 45 , 46 ], and is associated with good survival in patients treated with multidrug regimens [ 47 ]. It also predicts the response to the alkylating drug dacarbazine in metastatic CRC [ 48 , 46 ]. In this context, the data on MGMT methylation and expression reveals a complex pattern of regulation and argues against a complete silencing in a significant proportion of methylated cases.…”
Section: Discussionmentioning
confidence: 99%
“…PMS2 has been demonstrated to be important for GBM in various studies [31, 32]. Most interestingly, Walter and co-workers describe the case of a 13-year-old child presented with three simultaneous malignancies, including GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in patients who had received radiotherapy, low APE1 expression was significantly associated with decreased overall survival but was not significant in predicting survival in patients who had not received radiotherapy. 54 Furthermore, the significance of APE1 expression in breast cancer appears to be complex. Initial studies suggest that high APE1 expression indicates a poor prognosis in breast cancer, 55,56 whereas a more recent study conducted in a large cohort of breast cancers showed that low APE1 expression in estrogen receptor (ER)-positive tumors correlated with an aggressive phenotype and poor response to hormone therapy.…”
Section: Ape1mentioning
confidence: 99%